2005
DOI: 10.1108/14684520510628882
|View full text |Cite
|
Sign up to set email alerts
|

Data structuring and classification in newly‐emerging scientific fields

Abstract: The article addresses a methodological procedure based on keyword analysis and structuring of data into information systems in the field of functional foods as a newly emerging scientific field within the broader scope of food sciences and technology. Experiment was based on selection of a research field or research subject, selection of search profile, selection and processing of relevant databases, keyword analysis, and arranging of data (keywords) according to tree-structures. Keyword analysis was employed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Some of its widely used applications are the comparative evaluation of countries, universities, research institutes, and individual researchers. It may also be used for other purposes such as developing a better understanding of the structure of a scientific field or determining developments in the research area (Juvan et al ., ; Hall et al ., ; Waaijer and Palmblad, ).…”
mentioning
confidence: 97%
“…Some of its widely used applications are the comparative evaluation of countries, universities, research institutes, and individual researchers. It may also be used for other purposes such as developing a better understanding of the structure of a scientific field or determining developments in the research area (Juvan et al ., ; Hall et al ., ; Waaijer and Palmblad, ).…”
mentioning
confidence: 97%
“…Second, literature mapping techniques have been used to identify the emergence of new, and the evolution of established, themes in specific journals, including education (Erduran et al 2015), healthcare (Galer-Unti et al 2004), and medical sociology (Seale 2008). Third, and focusing specifically on keyword analysis, we found studies that identified the most frequently cited subject terms (Ribière and Walter 2013), the narrow or broad influence of key subject terms (Leite et al 2012), and the emergence of new subject areas within a discipline (Juvan et al 2005). Categorizing keywords thematically to identify the form and content of research areas is an established method (Juvan et al 2005;Seale 2008).…”
Section: Methodsmentioning
confidence: 95%
“…Third, and focusing specifically on keyword analysis, we found studies that identified the most frequently cited subject terms (Ribière and Walter 2013), the narrow or broad influence of key subject terms (Leite et al 2012), and the emergence of new subject areas within a discipline (Juvan et al 2005). Categorizing keywords thematically to identify the form and content of research areas is an established method (Juvan et al 2005;Seale 2008).…”
Section: Methodsmentioning
confidence: 97%
“…Portaluppi argues (on an example of chronobiologic references in medline ) that there exists important variability in the consistency of descriptors, and recommends the inclusion of some more commonly used concepts. Several attempts have been made to create more focused indexing and classification systems, for example, in newly emerging scientific fields . In our case, it is difficult to retrieve, for example, the documents on antiviral activity of any medicinal plant.…”
Section: Discussionmentioning
confidence: 99%
“…Several attempts have been made to create more focused indexing and classification systems, for example, in newly emerging scientific fields. 26 In our case, it is difficult to retrieve, for example, the documents on antiviral activity of any medicinal plant. A large proportion of records will still include only the most precise term, as generally suggested by database rules.…”
Section: Discussionmentioning
confidence: 99%